2022
DOI: 10.1021/acs.inorgchem.1c02876
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Hexanuclear Plutonium(IV) Nanostructure in an Acetate Solution via Visible–Near Infrared Absorption Spectroscopy, Extended X-ray Absorption Fine Structure Spectroscopy, and Density Functional Theory

Abstract: A new hexanuclear plutonium cluster has been stabilized in aqueous media with acetate ligands. To probe the formation of such a complex structure, visible−near infrared (vis− NIR) absorption spectroscopy, extended X-ray absorption fine structure (EXAFS) spectroscopy, and density functional theory ( D F T ) w e r e c o m b i n e d . T h e p r e s e n c e o f Pu 6 O 4 (OH) 4 (CH 3 COO) 12 species in solution was first detected by vis−NIR and EXAFS spectroscopy. To confirm unambiguously this structure, EXAFS spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 62 publications
3
12
0
Order By: Relevance
“…This suggested that bigger clusters could be formed from the assembly of those smaller molecular fragments. 5,[15][16][17][18] A better knowledge about the underlying mechanism would help in understanding the behaviour of these species in environmental context and pave the way for pioneering approaches devoted to the control of the size-property relationship of Pu nanomaterials. 13 Kinetic isotope effect (KIE) can be observed when comparing reaction rates in H 2 O and D 2 O.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This suggested that bigger clusters could be formed from the assembly of those smaller molecular fragments. 5,[15][16][17][18] A better knowledge about the underlying mechanism would help in understanding the behaviour of these species in environmental context and pave the way for pioneering approaches devoted to the control of the size-property relationship of Pu nanomaterials. 13 Kinetic isotope effect (KIE) can be observed when comparing reaction rates in H 2 O and D 2 O.…”
mentioning
confidence: 99%
“…1c) which offered striking similarities with a recently described oxo-hydroxo hexanuclear core of Pu(IV) cluster [Pu 6 (OH) 4 O 4 ] 12+ decorated by acetate or DOTA ligands. 15,16 Slight differences between both spectra were attributed to the decoration of the latter with acetate ligands (on-going efforts aim at stabilizing this species during Pu(IV) colloid synthesis). A similar observation in D 2 O appeared more complicated due to the important contribution of other Pu ionic species originated from Pu(IV) disproportionation and hydrolysis.…”
mentioning
confidence: 99%
“…Actually, in the visible spectra recorded with CaMWT at pH 6, the intense band at 456 nm followed by a shoulder at 475 nm and the double band at 659 and 686 nm were similar to the features identified for these hexanuclear Pu(IV) clusters. ,, DOTA, acetate, and glycine clusters present similar shells around Pu, two oxygen shells at 2.19 to 2.29 Å (two or four oxygen atoms, respectively) and at 2.36 to 2.42 Å (four, six, or seven oxygen atoms, respectively). The two shells of Pu(IV) are identical with four Pu(IV) in the axial plane at 3.76 to 3.77 Å and one Pu(IV) in the equatorial plane at 5.31 to 5.35 Å. The clusters decorated by acetate or glycine showed the presence of a water molecule in the Pu(IV) coordination sphere. , This water increased the number of oxygen atoms in the Pu–O shell but did do not change the main characteristics of the complex, notably the Pu(IV)–Pu(IV) distance, which is always shorter than in colloidal structures. , …”
Section: Resultsmentioning
confidence: 99%
“…Fourier transform was performed between 2.6 and 12 Å –1 (Figure (II)). These spectra are distinct from the spectra obtained with CaME-Pu and CaMWT-Pu samples at pH 7.4. Notable was the presence of an intense band around 3.7 to 3.8 Å, which is in the FT range characteristic of a Pu–Pu interaction, , suggesting that colloids or cluster cores were formed with CaMWT at pH 6.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, dicarboxylates like terephthalate connect these [M 6 O 8 ] building blocks to establish this class of 3D MOFs. The structural chemistry of single molecular [M 6 O 8 ] complexes has also been explored for M = Zr, Ce, Hf, Th U, Np, and Pu. As demonstrated in these examples, hydrolysis and associated complexation of M 4+ are of great interest in both fundamental science and various applications from chemical industries to nuclear energy systems.…”
Section: Introductionmentioning
confidence: 99%